2009
DOI: 10.1098/rspb.2009.0938
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic homogenization of woodland plant communities over 70 years

Abstract: Taxonomic homogenization (TH) is the increasing similarity of the species composition of ecological communities over time. Such homogenization represents a form of biodiversity loss and can result from local species turnover. Evidence for TH is limited, reflecting a lack of suitable historical datasets, and previous analyses have generated contrasting conclusions. We present an analysis of woodland patches across a southern English county (Dorset) in which we quantified 70 years of change in the composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
166
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(189 citation statements)
references
References 30 publications
12
166
10
1
Order By: Relevance
“…A similar pattern has been reported for weed vegetation [36] and woodlands [5], although they are a more stable environment. The increase in eutrophication leads to an increased proportion of generalists.…”
Section: Changes In Indicator Valuessupporting
confidence: 54%
“…A similar pattern has been reported for weed vegetation [36] and woodlands [5], although they are a more stable environment. The increase in eutrophication leads to an increased proportion of generalists.…”
Section: Changes In Indicator Valuessupporting
confidence: 54%
“…Our models predict that climate warming will lead to the increased domination of butterfly communities by a few generalist species, providing another example of biotic homogenisation (Keith et al 2009, Pino et al 2009, Ekroos et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have for instance found clear evidence for the importance of changes in forest management or canopy succession (e.g., Kirby and Thomas 2000;Van Calster et al 2008;Rogers et al 2008;Baeten et al 2009;Keith et al 2009), changed deer abundances (e.g., Kirby and Thomas 2000;Rooney et al 2004;Taverna et al 2005), increased atmospheric deposition of acidifying and eutrophying pollutants (e.g., Lameire et al 2000;Van Calster et al 2007;Baeten et al 2009;Keith et al 2009) or past habitat loss and fragmentation (e.g., Rogers et al 2009). For Lady Park Wood, canopy succession and deer (over)abundance are probably the main drivers.…”
Section: Discussionmentioning
confidence: 99%